The consistencies and inconsistencies between distal cholangiocarcinoma and pancreatic ductal adenocarcinoma: A systematic review and meta-analysis - Lv, Tian-Run; Wang, Ju-Mei; Ma, Wen-Jie; Hu, Ya-Fei; Dai, Yu-Shi; Jin, Yan-Wen; Li, Fu-Yu (Frontiers in Oncology, 2022)
Objective To evaluate the consistencies and inconsistencies between distal cholangiocarcinoma (DCCA) and pancreatic ductal adenocarcinoma (PDCA) regarding their biological features and long-term prognosis. Methods PubMed, the Cochrane Library, and EMBASE were searched to find comparative studies between DCCA and PDCA. RevMan5.3 and Stata 13.0 software were used for the statistical analyses. Results Eleven studies with 4,698 patients with DCCA and 100,629 patients with PDCA were identified. Pooled results indicated that patients with DCCA had a significantly higher rate of preoperative jaundice (p = 0.0003). Lymphatic metastasis (p < 0.00001), vascular invasion (p < 0.0001), and peri-neural invasion (p = 0.005) were more frequently detected in patients with PDCA. After curative pancreaticoduodenectomy (PD), a significantly higher R0 rate (p < 0.0001) and significantly smaller tumor size (p < 0.00001) were detected in patients with DCCA. Patients with DCCA had a more favorable overall survival (OS) (p < 0.00001) and disease-free survival (DFS) (p = 0.005) than patients with PDCA. However, postoperative morbidities (p = 0.02), especially postoperative pancreatic fistula (POPF) (p < 0.00001), more frequently occurred in DCCA. Conclusion Patients with DCCA had more favorable tumor pathological features and long-term prognosis than patients with PDCA. An early diagnosis more frequently occurred in patients with DCCA. However, postoperative complications, especially POPF, were more frequently observed in patients with DCCA.